STRUKTUR NARATIF TUTER CERITA “TONGTONGE” DARI SUMBAWA (Narrative Structure of “Tongtonge” Tuter Story from Sumbawa Island) - Erli Yetti (SAWERIGADING, 2015)
Indonesian regions are very rich with a variety of oral tradition. One is Batutir tradition from Sumbawa. Batutir is a relaxed story-telling tradition which tells while drink coffee. The story that’s still told today is Tongtonge, a humorous story. Indonesian regions are very rich with a variety of oral tradition. One is Batutir tradition from Sumbawa. Batutir is a relaxed story-telling tradition which tells while drink coffee. The story that’s still told today is Tongtonge, a humorous story. Tongtonge tale has a typical narrative structure whichis chanted in the form of poetry. The chant is similar to to the structure of the children’s song “Makan Apa” which in one sentence to another sentence continue to connect. In addition, Tongtone as a humorous story in Sumbawa story is called Gesah. The concerns i expressed in this research are 1) how is the narrative structure of the “Tongtonge” story, and 2) what values contained in the folk story? The purpose of this study is to investigate the narrative structure of the story “Tongtonge” as a way to make sense of the story so that the moral values and education into local wisdom in the story can be revealed. The method used is qualitative method. The theory used in this research is the theory of Axel Olrix. The expected result is the course of a study in which talking about the value of local knowledge of Sumbawa.